2022
DOI: 10.1609/aaai.v36i11.21466
|View full text |Cite
|
Sign up to set email alerts
|

Learning the Physics of Particle Transport via Transformers

Abstract: Particle physics simulations are the cornerstone of nuclear engineering applications. Among them radiotherapy (RT) is crucial for society, with 50% of cancer patients receiving radiation treatments. For the most precise targeting of tumors, next generation RT treatments aim for real-time correction during radiation delivery, necessitating particle transport algorithms that yield precise dose distributions in sub-second times even in highly heterogeneous patient geometries. This is infeasible with currently ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…While the sequential prediction of dose distributions is an important use case for treatment plan optimization, significantly higher prediction throughput and thereby average time per prediction can be achieved by predicting multiple samples in the one step. The deviation from faster prediction times reported for the DoTA model 17 high-end GPU used by the original authors. Depending on the available hardware in future studies, the achieved prediction times will therefore have to be re-evaluated.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…While the sequential prediction of dose distributions is an important use case for treatment plan optimization, significantly higher prediction throughput and thereby average time per prediction can be achieved by predicting multiple samples in the one step. The deviation from faster prediction times reported for the DoTA model 17 high-end GPU used by the original authors. Depending on the available hardware in future studies, the achieved prediction times will therefore have to be re-evaluated.…”
Section: Discussionmentioning
confidence: 95%
“…It was recently shown that the transformer architecture is very suitable for dose deposition predictions in the case of the proton beam therapy 17,19 . Transformer models rely on the prediction of sequences to sequences utilizing the so‐called attention mechanism 18 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations